Robotic assisted minimally invasive esophagectomy versus minimally invasive esophagectomy - Xue, Mengchao; Liu, Junjie; Lu, Ming; Zhang, Huiying; Liu, Wen; Tian, Hui (Frontiers in Oncology, 2024)
Background: Esophagectomy is the gold standard treatment for resectable esophageal cancer; however, there is insufficient evidence to indicate potential advantages over standard minimally invasive esophagectomy (MIE) in treating thoracic esophageal cancer. Robot-assisted minimally invasive esophagectomy (RAMIE) bridges the gap between open and minimally invasive surgery. In this single-center retrospective review, we compare the clinical outcomes of EC patients treated with MIE and RAMIE. Method: We retrospectively reviewed the clinical data of patients with esophageal cancer who underwent surgery at Qilu Hospital between August 2020 and August 2022, including 159 patients who underwent MIE and 35 patients who received RAMIE. The intraoperative, postoperative, and preoperative patient characteristics in both groups were evaluated.Results: Except for height, the MIE and RAMIE groups showed no significant differences in preoperative features (P>0.05). Further, there were no significant differences in intraoperative indices, including TNM stage of the resected tumor, tumor tissue type, or ASA score, between the two groups. However, statistically significant differences were found in some factors; the RAMIE group had a shorter operative time, less intraoperative bleeding, and more lymph nodes removed compared to the MIE group. Patients in the RAMIE group reported less discomfort and greater chest drainage on the first postoperative day than patients in the MIE group; however, there were no differences in other features between the two datasets. Conclusion: By comparing the clinical characteristics and outcomes of RAMIE with MIE, this study verified the feasibility and safety of RAMIE for esophageal cancer. Overall, RAMIE resulted in more complete lymph node clearance, shorter operating time, reduced surgical hemorrhage, reduced postoperative discomfort, and chest drainage alleviation in patients. To investigate the function of RAMIE in esophageal cancer, we propose undertaking a future clinical trial with long-term follow-up to analyze tumor clearance, recurrence, and survival after RAMIE.